2020
DOI: 10.1038/s41598-020-77443-x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of contraction rhythm homeostasis for hyperthermal sarcomeric oscillations of neonatal cardiomyocytes

Abstract: The heart rhythm is maintained by oscillatory changes in [Ca2+]. However, it has been suggested that the rapid drop in blood pressure that occurs with a slow decrease in [Ca2+] preceding early diastolic filling is related to the mechanism of rapid sarcomere lengthening associated with spontaneous tension oscillation at constant intermediate [Ca2+]. Here, we analyzed a new type of oscillation called hyperthermal sarcomeric oscillation. Sarcomeres in rat neonatal cardiomyocytes that were warmed at 38–42 °C oscil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 36 publications
0
30
0
1
Order By: Relevance
“…In a previous study, we found that in living cardiomyocytes, warming to a temperature close to body temperature can manifest sarcomeric oscillations [ 28 , 29 ]. Then, from a mathematical model that reproduces that phenomenon, it was estimated that warming the myofibrils could put the myofibrils into a sarcomeric oscillation state [ 29 , 31 , 32 ]. This time, we cannot say whether the mechanism is exactly the same as this estimation, but we succeeded in putting the myofibrils, which are no longer in the sarcomeric oscillation state at 25°C, into the sarcomeric oscillation state by warming them to 35°C.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a previous study, we found that in living cardiomyocytes, warming to a temperature close to body temperature can manifest sarcomeric oscillations [ 28 , 29 ]. Then, from a mathematical model that reproduces that phenomenon, it was estimated that warming the myofibrils could put the myofibrils into a sarcomeric oscillation state [ 29 , 31 , 32 ]. This time, we cannot say whether the mechanism is exactly the same as this estimation, but we succeeded in putting the myofibrils, which are no longer in the sarcomeric oscillation state at 25°C, into the sarcomeric oscillation state by warming them to 35°C.…”
Section: Resultsmentioning
confidence: 99%
“…1 d, e). The peak frequency became unsharp, and the periodic stability decreased due to the widening of the filament lattice spacing, the spatial limitation of the interaction between myosin and actin filaments, and the low probability of crossbridge formation [ 29 , 31 , 33 36 ]. The shortening of the A band, or myosin filament, reinforced this tendency by reducing the number of myosins that could form crossbridges ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations